Diagnosis of Abdominal Diseases Affecting Major Organs Using CT Image and YOLOV8 (International Journal of Preventive Medicine and Health (IJPMH), 2025)
This study investigates the YOLOv8 method, a popular object detection model, to detect abnormalities in abdominal CT scans. Our study leverages the sophisticated architecture and point-of- care detection capabilities of YOLOv8 to show that the model improves diagnostic accuracy and helps radiologists quickly identify potential panic cases